2015
DOI: 10.1016/j.athoracsur.2015.04.103
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Anesthetic Management of a Mediastinal Fatty Tumor: Lipoblastoma

Abstract: Lipoblastoma is a rare fatty tumor that is diagnosed almost exclusively in children. Presentation often consists of respiratory symptoms; chest computed tomography shows a hypodense, low, attenuated mediastinal mass. Surgical approach and anesthetic management are dependent on the location of the tumor and the degree of airway compression; in most cases, a thoracotomy is performed, although a sternotomy is used in selected cases. Final diagnosis can be confirmed using molecular genetic analysis; a genetic hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The oncogene PLAG1 (pleomorphic adenoma gene 1) is located on band 8q12. PLAG1 is activated by a breakpoint in the 8q11–13 region or polysomy of chromosome 8 [ 10 , 11 , 23 , 25 , 28 32 ]. Molecular analysis is important in the accurate diagnosis and optimum management.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncogene PLAG1 (pleomorphic adenoma gene 1) is located on band 8q12. PLAG1 is activated by a breakpoint in the 8q11–13 region or polysomy of chromosome 8 [ 10 , 11 , 23 , 25 , 28 32 ]. Molecular analysis is important in the accurate diagnosis and optimum management.…”
Section: Main Textmentioning
confidence: 99%
“…Close follow up for minimum of 5 years is recommended. Various studies have not reported any recurrences in completely excised tumors with follow ups of 2 months–10 years and median follow up times ranging from 38 to 42 months [ 11 , 14 , 15 , 19 , 22 , 24 , 25 , 27 , 30 ].…”
Section: Main Textmentioning
confidence: 99%
“…El cuadro clínico va a depender del tamaño y ubicación del tumor, pudiendo presentarse con síntomas respiratorios como también de manera asintomática 7 . El diagnóstico definitivo será dado por el estudio anátomo-patológico, pero se puede sospechar inicialmente con una adecuada anamnesis, examen físico y estudios imagenológicos.…”
Section: Introductionunclassified
“…Although these tumors are benign, they have a tendency to grow rapidly and impinge on and envelop surrounding structures, leading to symptoms. These tumors are most commonly associated with regions of immature adipose tissue in the soft tissue of the trunk and extremities, but they have also been shown to arise in the mediastinum, anterior chest, abdomen, neck, face, rectal area, and presacral region . There have been only case reports and case series in literature; however, the mainstay of treatment relies on surgical excision unless extreme circumstances are present .…”
Section: Introductionmentioning
confidence: 99%